Jumpstart to skinny : the simple 3-week plan for supercharged weight loss - Harper, Bob (Ballantine Books, 2013)
"Jumpstart to Skinny features thirteen short-term Rules (no one gets thin on mere suggestions) that will supercharge your weight loss. Taking any confusion or decision making out of the equation, Harper also provides a day-by-day plan for success, including his body-toning "Jumpstart Moves" and deliciously slimming recipes specially designed for your get-skinny needs. Jumpstart to Skinny lets you in on the secrets Bob shares with his red-carpet celebrity clients. This is not a marathon diet; it's a quick sprint to the finish line. And the victory lap comes when you slip into that sexy dress or swimsuit and feel fantastic."--